Development of an external-to-internal convertible endoscopic biliary drainage device – a preliminary prospective feasibility study - Mori, Akihiro; Ito, Shun; Yumura, Takayuki; Hachiya, Hiroki; Sawada, Masashi; Hayashi, Shintaro; Ohashi, Noritsugu (Endoscopy International Open, 2018)
Background and study aims Endoscopic nasobiliary drainage (ENBD) for a malignant stricture in the bile duct has some advantages over endoscopic biliary stenting (EBS). However, ENBD may cause nasopharyngeal discomfort. We developed an external-to-internal convertible endoscopic biliary drainage (ETI-EBD) device that enables both internal and external drainage to occur during a single endoscopy.Patients and methods This device consists of three parts, comprising a 5-Fr ENBD tube (250 cm) (ENBD-t), an 8.5-Fr EBS tube (7 cm) (EBS-t), and an 8-Fr pusher tube for EBS (230 cm) (P-t). The EBS-t is mounted over the ENBD-t at the distal end of the ENBD-t. The P-t is also placed over the ENBD-t. After an endoscopic sphincterotomy, the EBS-t of the device is inserted into the papilla, then the duodenal endoscope is withdrawn, leaving the device in place. After ENBD, only the ENBD-t was withdrawn from the P-t. At this point, the EBS-t was isolated and left without endoscopy or radiography. Results ETI-EBD was successfully placed in all consecutive 21 patients (100 %). The release of EBS-t from ENBD-t wit was successfully completed in 19 patients (90.5 %). There were 4 patients with kink of P-t when exchanging this device from the mouth to the nose. It was difficult for 2 patients to withdraw the ENBD-t because of poor lubrication performance. There were no significant complications associated with the use of the device.Conclusion This device allows for both external and internal biliary drainage with a single endoscopy.